2005
DOI: 10.1038/sj.npp.1300842
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mecamylamine on Trigeminal and Olfactory Chemoreception of Nicotine

Abstract: Nicotine presented to the nasal cavity at low concentrations evokes 'odorous' sensations, and at higher concentrations 'burning' and 'stinging' sensations. A study in smokers and nonsmokers provided evidence of a relationship between the experience with the pharmacological action of S-(À)-nicotine and the perceived pleasantness/unpleasantness following nasal stimulation with S-(À)-nicotine. Mecamylamine, a nicotinic acetylcholine-receptor-(nAch-R) antagonist, was able to block painful responses following chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
(50 reference statements)
0
30
0
Order By: Relevance
“…Because nicotine activates capsaicin-sensitive trigeminal neurons (4,7), the contribution of somatosensory input was tested by measuring behavioral responses to nicotine in adult KO animals that had been injected with capsaicin as neonates. This treatment produces systemic and life-long elimination of the majority of capsaicin-sensitive neurons, causing deficits in chemonociceptive reactivity (28).…”
Section: Resultsmentioning
confidence: 99%
“…Because nicotine activates capsaicin-sensitive trigeminal neurons (4,7), the contribution of somatosensory input was tested by measuring behavioral responses to nicotine in adult KO animals that had been injected with capsaicin as neonates. This treatment produces systemic and life-long elimination of the majority of capsaicin-sensitive neurons, causing deficits in chemonociceptive reactivity (28).…”
Section: Resultsmentioning
confidence: 99%
“…By specific we mean processes in which the key step relies on the irritant possessing a narrowly tuned chemical structure, functionality, or conformation that when even slightly modified produces a dramatic change in activity. There are some prototypical irritants, usually active at much lower concentrations than general VOCs, that fit tightly and activate strongly a particular receptor, e.g., nicotine (Alimohammadi and Silver 2000;Thuerauf et al 2006), capsaicin (Bae et al 2004;Silver et al 2006), isothiocyanates and thiosulfinates (Bautista et al 2006), and menthol (Bandell et al 2006), but even these "specific" receptors often display broad chemical selectivity (Trevisani et al 2002;Macpherson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…VOCs that are reactive towards tissue may also produce nociception by damaging cells and producing secondary release of endogenous chemical mediators activating various ion channels, such as acid sensing ion channels (ASIC), purinergic receptor subtype X channels (P2X), and serotonin ionotropic receptors (Rang et al, 1991, Wood and Docherty, 1997, McCleskey and Gold, 1999, Lee et al, 2005. Pharmacological and molecular-biology studies have identified a number of likely chemesthetic receptors such as the nicotine (Thuerauf et al, 1999, Alimohammadi and Silver, 2000, Thuerauf et al, 2006, capsaicin (Walpole et al, 1996), and menthol (Eccles, 1994, Peier et al, 2002 receptors. The last two receptors are also thermoreceptors responding to warm/ hot and cool/cold temperatures, respectively (Caterina et al, 1997, McKemy et al, 2002.…”
Section: Introductionmentioning
confidence: 99%